Modulation of K(2P)2.1 and K(2P)10.1 K(+) channel sensitivity to carvedilol by alternative mRNA translation initiation - Kisselbach, J (Br J Pharmacol, 2014)
BACKGROUND AND PURPOSE: The β-receptor antagonist carvedilol blocks a range of ion channels. K(2P)2.1 (TREK1) and K(2P)10.1 (TREK2) channels are expressed in the heart and regulated by alternative translation initiation (ATI) of their mRNA, producing functionally distinct channel variants. The first objective was to investigate acute effects of carvedilol on human K(2P)2.1 and K(2P)10.1 channels. Second, we sought to study ATI-dependent modulation of K(2P) K(+) current sensitivity to carvedilol. EXPERIMENTAL APPROACH: Using standard electrophysiological techniques, we recorded currents from wild-type and mutant K(2P)2.1 and K(2P)10.1 channels in Xenopus oocytes and HEK 293 cells. KEY RESULTS: Carvedilol concentration-dependently inhibited K(2P)2.1 channels (IC(50)(,oocytes) = 20.3 μM; IC(50)(,)(HEK) = 1.6 μM) and this inhibition was frequency-independent. When K(2P)2.1 isoforms generated by ATI were studied separately in oocytes, the IC(50) value for carvedilol inhibition of full-length channels (16.5 μM) was almost 5-fold less than that for the truncated channel variant (IC(50) = 79.0 μM). Similarly, the related K(2P)10.1 channels were blocked by carvedilol (IC(50)(,oocytes) = 24.0 μM; IC(50)(,)(HEK) = 7.6 μM) and subject to ATI-dependent modulation of drug sensitivity. CONCLUSIONS AND IMPLICATIONS: Carvedilol targets K(2P)2.1 and K(2P)10.1 K(+) channels. This previously unrecognized mechanism supports a general role of cardiac K(2P) channels as antiarrhythmic drug targets. Furthermore, the work reveals that the sensitivity of the cardiac ion channels K(2P)2.1 and K(2P)10.1 to block was modulated by alternative mRNA translation initiation.